A review on linear regression - Raxmatova, Anora (Журнал математики и информатики, 2022)
In this study, analytical and approximate solutions were obtained for the encroachment of regression coefficients by looking at the model of nonlinear regression using some of the trigonometric functions. The application of the obtained nonlinear regression function in machine learning has been studied.